Manajemen Kurikulum dan Pembelajaran Bahasa Arab - Deddy Ramdhani (The Center for Language Development, Mataram State Islamic University., 2020)
This study aims to describe the implementation of Arabic language learning, teaching staffs, curriculum planning, and the Arabic language learning evaluation. This study was a field research with descriptive qualitative analysis, and a phenomenological approach. The data was collected through observation, interview, and documentation. To test the validity of the study, triangulation. The result of the study showed that; First, the process of Arabic language learning was based on the learning components of acquiring the capability on becoming an active speaker through kitabah, qiroh, simaah and the ability to examine and analyze Al-Qur’an and As-sunnah. The learning method was conveyed through speech, question and answer, qowaid, direct method, and practice at language laboratory. Textbook, whiteboard, laptop, were employed as the learning media for teaching. The learning evaluation was tested through pre-test, and post-test in direct learning, formative and summative assessment. Second, administration test, written test, oral, and teaching Arabic language practice, preferably Islamic boarding school alumni, and Arabic language-based graduate qualification, well act, and loyal were conducted to prepare the qualified teaching staffs. To increase the competence; seminar, workshop method, Arabic language learning, and training learning. Third, planning for the Arabic language learning curriculum with annual program preparation, semester program as the reference for conducting teaching and syllabus, and RPP planning were implemented as teachers’ guidance for teaching in the classroom setting. Fourth, the Arabic language learning curriculum evaluation was conducted, yet, it was not maximally performed.